Developing Lithium Chemistry of 1, 2‐Dihydropyridines: From Kinetic Intermediates to Isolable Characterized Compounds. Issue 41 (31st August 2015) - Armstrong, David R.; Harris, Catriona M. M.; Kennedy, Alan R.; Liggat, John J.; McLellan, Ross; Mulvey, Robert E.; Urquhart, Matthew D. T.; Robertson, Stuart D.
Abstract Generally considered kinetic intermediates in addition reactions of alkyllithiums to pyridine, 1‐lithio‐2‐alkyl‐1, 2‐dihydropyridines have been rarely isolated or characterized. This study develops their "isolated" chemistry. By a unique stoichiometric (that is, 1:1, alkyllithium/pyridine ratios) synthetic approach using tridentate donors we show it is possible to stabilize and hence crystallize monomeric complexes where alkyl is tert‐butyl. Theoretical calculations probing the donor‐free parent tert‐butyl species reveal 12 energetically similar stereoisomers in two distinct cyclotrimeric (LiN)3 conformations. NMR spectroscopy studies (including DOSY spectra) and thermal volatility analysis compare new sec‐butyl and iso‐butyl isomers showing the former is a hexane soluble efficient hydrolithiation agent converting benzophenone to lithium diphenylmethoxide. Emphasizing the criticalness of stoichiometry, reaction of nBuLi/Me6TREN with two equivalents of pyridine results in non‐alkylated 1‐lithio‐1, 4‐dihydropyridine⋅Me6TREN and 2‐n‐butylpyridine, implying mechanistically the kinetic 1, 2‐n‐butyl intermediate hydrolithiates the second pyridine.